The Effect of Credit Risk Management, Bank-Specific Factors, and Corporate Social Responsibility on the Financial Performance of Banks in Indonesia - Putri, Agissa Ardania; Nalurita, Febria; Hamdy (Universitas Trisakti, 2024)
This research aims to analyze the effects of credit risk management measured by NPL and CAR, bank-specific factors measured by CER and LDR, CSR, and bank size on the financial performance of public banks listed in the BEI 2017-2022 period. Sample in this research as many 27 Public Bank with a total of 162 observations and the technique of sampling used purposive sampling. The analysis data method used regression panel data with the e-views program. The results of this research show that credit risk management with measured NPL has a negative significant effect on financial performance with measured NPM, while credit risk management measured by CAR has a positive significant effect on financial performance. Bank Specific Factors measured by CER and LR have a negative and significant effect on financial performance, while CSR has no effect on financial performance and Bank Size has a positive and significant effect on financial performance. Investors can use the results of this study to analyze the management of banking management and become a consideration in making investment decisions. Improving the financial performance of the bank can be enhanced through a focus on risk management, cost efficiency, and liquidity, which enables management to carry out better performance management.